Admixed ancestral composition with Amerindian predominance at the Peruvian Alzheimer Disease Initiative (PeADI). (20th December 2022) - Cubas‐Montecino, Diana; Rajabli, Farid; Illanes‐Manrique, Maryenela; Kushch, Nicholas A.; Mena, Pedro Ramon; Whitehead, Patrice L.; Hamilton‐Nelson, Kara L.; Milla‐Neyra, Karina; Marca, Victoria; Sarapura‐Castro, Elison; Manrique‐Enciso, Carla; Mejía, Koni K.; et al.
Abstract: Background: Current genetic studies for AD and other dementias are making efforts to incorporate underrepresented populations including admixed Latinos. Peruvian population is characterized by admixed ancestry with a significant Amerindian component, which varies according to specific regions across Peru. The Peruvian Alzheimer Disease initiative (PeADI) was developed to ascertain a cohort for AD and other related dementias for genetic studies in Peru. We aim to determine the patterns of continental ancestry by regions across Peru. Methods: Over the last 3 years, The PeADI study has recruited 212 unrelated cognitive participants through collaborative health centers and community outreach ascertainment strategies. Cases were assessed by neurologists following NINDS‐ADRDA criteria. Controls were screened using MMSE, Clock drawing test and Pfeffer functional activities questionnaire. Genome‐wide genotyping was performed by Illumina screening array. PC‐AiR and model‐based. The cohort was divided into five regions (Northern, Southern, Lima, Central Highlands, and Amazonian) based on place of birth of the participant or the ancient known ancestor. Results: The global Admixture analysis showed that Peruvians have a substantial Amerindian component (63.6%), followed by European (35.9%), African (2.5%) and East Asian (2.1%) components. When analyzed by regions, we found that the Central region concentrates the highest Amerindian ancestry (72.7%), followed by the Northern region (58.2%), Lima and Callao (57%), the Amazonian region (55.6%), and the Southern region (55.1%). The highest European ancestry is located in the Amazonian region (42.1%), while the Central region has the lowest (26.6%). African and East Asian ancestry has little influence in Peru, being the Northern with the higher African component (4.1%), and Lima and Callao the region with the higher East Asian component (3.5%). There is no significant for Amerindian component across five regions (p=0.054); however, Central highlands region has higher Amerindian component compared to Lima (p=0.005), the Northern (p=0.005) and Southern(p=0.017) regions. Conclusion: Our results confirmed the ancestry admixture of the Peruvian population with predominance of the Amerindian component. The Central region concentrates the highest Amerindian ancestry compared with other regions across Peru.